Equity in practice? Evaluations of equity in planning for bus rapid transit. (July 2018) - Linovski, Orly; Baker, Dwayne Marshall; Manaugh, Kevin
Highlights: Equity concerns were rarely considered in the planning stages for BRT. Most actors' definition of equity did not acknowledge disadvantaged communities. BRT seen as a tool to change urban form, often in conflict with equity goals. Abstract: The distribution of transportation benefits is mediated through planning professionals and elected officials, who frame the goals of these investments and can prioritize the importance of fairness in decision-making. Despite increasing evidence of the importance of transportation equity, there are broad questions about how equity principles factor into planning processes. This work provides an empirical analysis of the role of transit equity in planning for BRT investments in three Canadian metropolitan areas. Our findings show that transit equity rarely figured into the design and planning of BRT systems and there is a lack of clarity in both defining equity and determining how it should be integrated in planning processes. Most definitions of transit equity focused on the equal distribution of resources for all groups, rather than consideration of transit-dependent riders. Equity outcomes were also in conflict with other goals, as BRT systems were viewed largely as a tool for encouraging development and focused on attracting car drivers to transit. This paper argues that there needs to be a better understanding of the values and priorities of those involved in professional and political decision-making processes if transit equity goals are to be realized.